2008
DOI: 10.1002/da.20292
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic dysfunction and the psychopharmacology of posttraumatic stress disorder

Abstract: The catecholamine norepinephrine is a critical effector of the mammalian stress response and has been implicated in the pathophysiology of posttraumatic stress disorder (PTSD)-a syndrome intrinsically related to the experience of extraordinary stress. Symptom-linked hypernoradrenergic derangements have been observed in PTSD and several studies have examined the potential therapeutic effects of agents that dampen the centrally hyperactive noradrenergic state. These agents include compounds that decrease norepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
151
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(162 citation statements)
references
References 91 publications
7
151
0
4
Order By: Relevance
“…This leads to reexperiencing memories of the original trauma and causes early hyperaroused psychophysiological responses and, with time, turns into a late ''numbing'' experience (when circulating NE and cortisol are actually low perhaps due to a ''burn-out'' state). [48] The efficacy of the a1 antagonist prazosin, the a2 agonist clonidine, and the b antagonist propanolol in the clinical treatment of early PTSD provide the evidence of an involvement of a dysfunctional central NE system in early trauma-related syndromes. [48][49][50][51] There is substantial evidence to show that the sleep problems and nightmares that are seen in PTSD may be secondary to hyperactivity of the noradrenergic systems during the earlier acute stages of the trauma and thus prazosin, a selective a1 noradrenergic antagonist, was shown to provide clinical benefit.…”
Section: Chronic Stress and Ne Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to reexperiencing memories of the original trauma and causes early hyperaroused psychophysiological responses and, with time, turns into a late ''numbing'' experience (when circulating NE and cortisol are actually low perhaps due to a ''burn-out'' state). [48] The efficacy of the a1 antagonist prazosin, the a2 agonist clonidine, and the b antagonist propanolol in the clinical treatment of early PTSD provide the evidence of an involvement of a dysfunctional central NE system in early trauma-related syndromes. [48][49][50][51] There is substantial evidence to show that the sleep problems and nightmares that are seen in PTSD may be secondary to hyperactivity of the noradrenergic systems during the earlier acute stages of the trauma and thus prazosin, a selective a1 noradrenergic antagonist, was shown to provide clinical benefit.…”
Section: Chronic Stress and Ne Activitymentioning
confidence: 99%
“…[48] The efficacy of the a1 antagonist prazosin, the a2 agonist clonidine, and the b antagonist propanolol in the clinical treatment of early PTSD provide the evidence of an involvement of a dysfunctional central NE system in early trauma-related syndromes. [48][49][50][51] There is substantial evidence to show that the sleep problems and nightmares that are seen in PTSD may be secondary to hyperactivity of the noradrenergic systems during the earlier acute stages of the trauma and thus prazosin, a selective a1 noradrenergic antagonist, was shown to provide clinical benefit. [52][53][54][55] Taken together, these findings suggest that traumatic stress results in a hyperactive central NE system and exaggerated central nervous system responses (i.e., sensitization) to noradrenergic activation.…”
Section: Chronic Stress and Ne Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given that research has consistently demonstrated increased noradrenergic tone in both adults (for review see) 16) and youth with PTSD, 17) several investigators have explored the efficacy of anti-adrenergic agents for the prevention and treatment of PTSD. Propranolol is a centrally-acting, long-chain β-blocker that is used primarily for hypertension, and has been used off-label for the treatment of situational anxiety, such a stage fright or performance anxiety.…”
Section: Propranololmentioning
confidence: 99%
“…The noradrenergic system is activated upon stress, resulting in increased release of norepinephrine primarily from the locus coeruleus to its many projection sites that modulate stress responses and emotional behaviors, including the amygdala, hippocampus, hypothalamus and PFC, all of which constitute the LC-NE system (Aston- Jones and Cohen, 2005;Strawn and Geracioti, 2008). The activation of the LC-NE system under acute stress leads to generation and transmission of negative emotional memories starting from the amygdala, a process that can be inhibited by blocking norepinephrine activity (Charney, 2004).…”
Section: Noradrenergic and Dopaminergic Systemsmentioning
confidence: 99%